Coagulation: At the heart of infective endocarditis. (3rd February 2020) - Liesenborghs, Laurens; Meyers, Severien; Vanassche, Thomas; Verhamme, Peter
Abstract: Infective endocarditis is a life‐threatening and enigmatic disease with a mortality of 30% and a pathophysiology that is poorly understood. However, at its core, an endocarditis lesion is mainly a fibrin and platelet blood clot infested with bacteria, clinging at the cardiac valves. Infective endocarditis therefore serves as a paradigm of immunothrombosis gone wrong. Immunothrombosis refers to the entanglement of the coagulation system with innate immunity and the role of coagulation in the isolation and clearance of invading pathogens. However, in the case of infective endocarditis, instead of containing the infection, immunothrombosis inadvertently creates the optimal shelter from the immune system and allows some bacteria to grow almost unimpeded. In every step of the disease, the coagulation system is heavily involved. It mediates the initial adhesion of bacteria to the leaflets, fuels the growth and maturation of a vegetation, and facilitates complications such as embolization and valve destruction. In addition, the number one cause of infective endocarditis, Staphylococcus aureus, has proven to be a true manipulator of immunothrombosis and thrives in the fibrin rich environment of an endocarditis vegetation. Considering its central role in infective endocarditis, the coagulation system is an attractive therapeutic target for this deadly disease. There is, however, a very delicate balance at play and the use of antithrombotic drugs in patients with endocarditis is often accompanied with a high bleeding risk.